Arabidopsis ketoacyl‐CoA synthase 16 (KCS16) forms C36/C38 acyl precursors for leaf trichome and pavement surface wax. (21st July 2017) - Hegebarth, Daniela; Buschhaus, Christopher; Joubès, Jérôme; Thoraval, Didier; Bird, David; Jetter, Reinhard
Abstract: The aliphatic waxes sealing plant surfaces against environmental stress are generated by fatty acid elongase complexes, each containing a β ‐ketoacyl‐CoA synthase (KCS) enzyme that catalyses a crucial condensation forming a new C─C bond to extend the carbon backbone. The relatively high abundance of C35 and C37 alkanes derived from C36 and C38 acyl‐CoAs in Arabidopsis leaf trichomes (relative to other epidermis cells) suggests differences in the elongation machineries of different epidermis cell types, possibly involving KCS16, a condensing enzyme expressed preferentially in trichomes. Here, KCS16 was found expressed primarily in Arabidopsis rosette leaves, flowers and siliques, and the corresponding protein was localized to the endoplasmic reticulum. The cuticular waxes on young leaves and isolated leaf trichomes of ksc16 loss‐of‐function mutants were depleted of C35 and C37 alkanes and alkenes, whereas expression of Arabidopsis KCS16 in yeast and ectopic overexpression in Arabidopsis resulted in accumulation of C36 and C38 fatty acid products. Taken together, our results show that KCS16 is the sole enzyme catalysing the elongation of C34 to C38 acyl‐CoAs in Arabidopsis leaf trichomes and that it contributes to the formation of extra‐long compounds in adjacent pavement cells. Abstract : Our findings are a major step forward in our understanding of (Arabidopsis) cuticular wax formation, as they (1) extend the previously reported biosynthesis pathways; (2) provide detail on the functional diversification of a fairly big (21 homologues in Arabidopsis) and not well understood gene family; (3) detail the cell‐type‐specific and development‐specific control of wax formation and composition for the first time; and thus (iv) manifest the degree of genetic control over wax chemical diversity. Clearly, this raises very interesting questions regarding the biological functions exerted by trace components of the complex wax mixtures and therefore the functional relevance of chemical diversity in plant lipids in general.